Biographical Studies of G.I. Gurdjieff. (1st August 2016) - Azize, Joseph
Abstract : The various published biographies and biographical notices of G.I. Gurdjieff (c.1865-1949) are of diverse style, quantity and content. While some have made considerable contributions to the subject, most attempts have reacted for or against Gurdjieff's status as what might call an 'Enlightened Master'. Little biographical writing on Gurdjieff has questioned the scope, reliability and prejudices of the sources. Further, possible resources have been neglected. The development in Gurdjieff's ideas is often overlooked, his life is not sufficiently related to that development, and the lack of comparative research has failed to highlight Gurdjieff's unique contributions. This article is structured in four parts. The first is an introduction, followed by an overview of existing biographical studies of Gurdjieff. The third part addresses bias in these studies, and this is followed by suggestions for future studies. It is concluded that fieldwork regarding the biography of Gurdjieff has been hampered by imperfect methodology. However, with better use of the source material, some of which has only recently been discovered, and a rigorous use of sources, a more balanced and nuanced picture of Gurdjieff's life, and the development of his ideas and methods, should emerge.